Performance Evaluation of Growth Mutual Fund Schemes in India - Singh, Rajkumar Giridhari; Mishra, Samikshya (Indian Journal of Research in Capital Markets, 2019)
The paper examined the performance of growth mutual fund schemes relative to the benchmark index in India. Monthly net assets value (NAV) of five open-ended growth schemes were taken as a sample of the study covering a period of 5 years, that is, April 2012 to March 2017. The average return, standard deviation (risk), and beta were calculated for the selected schemes. Three performance analysis measures, that is, Treynor ratio, Sharpe ratio, and Jensen’s alpha were calculated from the obtained data. Sixty percent of the schemes were found to outperform the market, while 40% had underperformed the market. It is anticipated that the performance measurement results will be helpful to the investors in the future in deciding their investment. The study delved upon the portfolio performance not only on the returns of the funds, but also considered the measures of risk. The basic objective of this performance evaluation was to identify whether the selected funds performed better than the market index or not.